EXPERIMENTAL STUDY ON THE EFFECTIVENESS OF ADAPTIVE PROGRAMMING INSTRUCTION FOR FUTURE INFORMATICS TEACHERS - Tekesbayeva, N.A.; Oshanova, N.T.; Bukanova, A.; Baizakova, Е.М.; Kami, A.E. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This article addresses the organization of adaptive learning in the context of a digital educational environment at a higher educational institution. It presents the VARK learning style model by N. Fleming, which is based on individual psychological characteristics of cognitive structures and predispositions toward different methods of interaction with educational content. The methodology of J. Bruner is also explored, supporting the differentiation of learning according to the primary type of thinking and defining an individual approach to the analytical-synthetic processing of educational information. Based on these theories, a model of adaptive education in programming for students in the «Informatics» field was developed and implemented. As part of the implementation, digital educational modules were created and integrated into the Knan Academy platform. During the experimental trial, students participated in courses where the content was adapted to their cognitive styles, resulting in a 15% average increase in academic performance and improved comprehension of complex topics, such as working with algorithms and data structures. The results of the study demonstrate that the proposed model enhances the quality of the educational process and deepens students' mastery of programming while effectively adapting learning to individual needs. The significance of the study lies in providing a theoretical and practical foundation for the use of digital technologies as a tool for adaptive learning, contributing to the development of the scientific and educational environment in the context of digital education